Morphoanatomy and biochemistry of seeds of Dicypellium caryophyllaceum (Lauraceae) at different stages of fruit maturation - Dhyene Rayne dos Santos Becker; Raírys Cravo Herrera; Tainá Teixeira Rocha; Fábio Miranda Leão; Alisson Rodrigo Souza Reis; Roberto Cezar Lobo da Costa; Lenaldo Muniz de Oliveira; Marilza Neves do Nascimento (Rodriguésia)
Abstract The “pau-cravo” (Dicypellium caryophyllaceum) is a tree species of the family Lauraceae, native to the Amazon rainforest. As a result of overexploitation during the last few centuries, D. caryophyllaceum has become extremely rare in Brazil. Taking into account the importance of basic and advanced studies of seeds and the scarce information about this species, the goal of the present study was to define morphological markers of seed developmental stages and to understand the dynamics of reserve deposition in D. caryophyllaceum seeds. The species produces a drupe-like fruit due to the presence of a rigid endocarp, as revealed by anatomic examination. The analysis of biochemical properties in mature seeds of D. caryophyllaceum showed a lipid content of 19%, being classified as oleaginous. Changes were observed in the contents of proteins, sugars, and starch throughout the maturation stages, with the highest values of Total Soluble Sugars (4.01%) and Reducing Sugars (3.22%) observed in seeds at stage I. The highest values of amino acids (0.13%) and starch (9.5%) were detected in mature fruit (stage II). Biochemical and morphological information from the seeds is relevant for planning conservation, observation, and restoration strategies.